Fluid flow and methane occurrences in the Disko Bugt area offshore West Greenland: indications for gas hydrates? - Nielsen, Tove; Laier, Troels; Kuijpers, Antoon; Rasmussen, Tine Lander; Mikkelsen, Naja E.; Nørgård-Pedersen, Niels (Geo-Marine Letters, 2014)
This is a pre-print of an article published in Geo-Marine Letters. The final authenticated version is available online at https://doi.org/10.1007/s00367-014-0382-2 The present study is the first to directly address the issue of gas hydrates offshore West Greenland, where numerous occurrences of shallow hydrocarbons have been documented in the vicinity of Disko Bugt (Bay). Furthermore, decomposing gas hydrate has been implied to explain seabed features in this climate-sensitive area. The study is based on archive data and new (2011, 2012) shallow seismic and sediment core data. Archive seismic records crossing an elongated depression (20×35 km large, 575 m deep) on the inner shelf west of Disko Bugt (Bay) show a bottom simulating reflector (BSR) within faulted Mesozoic strata, consistent with the occurrence of gas hydrates. Moreover, the more recently acquired shallow seismic data reveal gas/fluid-related features in the overlying sediments, and geochemical data point to methane migration from a deeper-lying petroleum system. By contrast, hydrocarbon signatures within faulted Mesozoic strata below the strait known as the Vaigat can be inferred on archive seismics, but no BSR was visible. New seismic data provide evidence of various gas/fluid-releasing features in the overlying sediments. Flares were detected by the echo-sounder in July 2012, and cores contained ikaite and showed gas-releasing cracks and bubbles, all pointing to ongoing methane seepage in the strait. Observed seabed mounds also sustain gas seepages. For areas where crystalline bedrock is covered only by Pleistocene–Holocene deposits, methane was found only in the Egedesminde Dyb (Trough). There was a strong increase in methane concentration with depth, but no free gas. This is likely due to the formation of gas hydrate and the limited thickness of the sediment infill. Seabed depressions off Ilulissat Isfjord (Icefjord) previously inferred to express ongoing gas release from decomposing gas hydrate show no evidence of gas seepage, and are more ...